DEVELOPMENT OF MODIFIED DOMINO CARD LEARNING MEDIA IN SCIENCE LEARNING MATERIAL ON ANIMAL LIFE CYCLES FOR GRADE V ELEMENTARY SCHOOL STUDENTS - Febriani, Dea Salma; Arini, Novanita Whindi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
This research was conducted through interviews with classroom teachers to identify the difficulties in developing instructional media that led them to more frequently use existing media in the teaching and learning process. This situation can lead to boredom during learning. The objectives of this study are to enhance learning media using modified domino cards and to assess its suitability in teaching Natural Sciences (IPA), particularly focusing on the animal life cycle material. This research employs the Research and Development (R&D) method with the PPE model, encompassing three stages: planning, production, and evaluation. The research was carried out at SDN Baru 02 Pagi. Data collection for this study involved questionnaires distributed to media experts, content experts, education experts, and students, allowing them to assess the suitability of the modified domino card media. The evaluation results from media experts indicated a score of 80% in the "adequate" category, whereas content experts and education experts assigned a score of 92% in the "highly feasible" category. Additionally, the questionnaire results from students in the small-scale trial yielded a score of 79% in the "adequate" category. In the large-scale trial, the score reached 85% in the "highly feasible" category. Based on the attained results, the modified domino card media has demonstrated its effectiveness in enhancing the understanding of animal life cycles.